The complete mitochondrial genome of Daurian jackdaw (Corvus dauuricus) - Zhao, Chao (Mitochondrial DNA B Resour, 2020)
In this study, the complete mitochondrial genome of Daurian jackdaw (Corvus dauuricus, Pallas, 1776) was sequenced and deposited to GeneBank for the first time using muscle tissue. This mitochondrial genome is a circular molecule of 16921 bp in length and sequence analysis showed it contains 2 rRNA genes, 22 tRNA genes, 13 protein-coding genes and D_loop. The phylogenetic analysis basis of 12 protein-coding genes except for ND6 gene of 13 species shows that most of the genus of Corvus were grouped into two clades, and C. dauuricus was basal to all other Corvus.